FY2018 : Output Cost Estimates and Budget Outturn. (Policy Papers; Policy Paper ;, 2018)
The Fund continues to make efforts to maximize the use of available resources in order to deliver on the priorities and initiatives laid out in the Global Policy Agenda (GPA). The FY 18 outturn reflects reallocations and efficiency gains, as well as flexibility provided by carry forward resources. With the number of Fund arrangements falling, the Fund's outputs shifted from spending on lending activity to multilateral surveillance. On the input side, the structural budget was fully utilized. This paper presents key highlights of the FY 18 outturn, including a discussion of the outputs and inputs. Details on Capacity Development (CD) are presented in Annex.